Specialization and Modularity of a Bat Fly Antagonistic Ecological Network in a Dry Tropical Forest in Northern Colombia - Durán de la Ossa, Adrián Alonso (2018)
Ecological networks represent the energy flow and interactions among the species of an ecological community. Streblidae is a family of bloodsucking flies specialized in parasitizing bats, thus forming an ecological network. The purpose of this study was to investigate the specialization and modularity of a bat fly antagonist ecological network in a tropical dry forest in northern Colombia. Bat hosts were sampled by using mist nets, while bat flies were collected directly from the hosts by using entomological forceps. The network was built with the Bipartite package from R software. The sampling effort resulted in 270 bat flies recorded on 45 host individuals. The network showed a high specialization (H' 2 = 0.67) and a low connectance (C = 0.30). Paradyschiria parvuloides was the most specialized fly (d = 0.95). The interactions exhibited a high modularity (Q = 0.57), with five modules. This study confirms the high specialization between bats and Streblidae flies, which is influenced by factors such as fidelity to the refuge and habitat, and host abundance.